Analisis Kinerja Keuangan Dengan Pendekatan Economic Value Added Pada PT. Bank Muamalat Indonesia Tbk. - Karnila Ali; Ardiansyah Japlani; Naelia Zaini (Universitas Muhammadiyah Metro, 2024)
Measurement based on financial ratios is very dependent on the accounting method or treatment used in preparing the company's financial statements, so often the company's performance looks good and increases, actually performance does not increase and even decreases. To overcome these problems, performance measurement can be used with an Economic Value Added (EVA) approach to measure performance based on value or measure economic added value generated by the company as a result of management activities or strategies. Based on the research objectives, is descriptive research with a quantitative approach. The design used is descriptive analytics, a research method where a researcher identifies and measures variables, researchers also look for relationships between variables to explain the observed event or phenomenon. This study analyzes the financial performance of PT. Bank Muamalat Indonesia Tbk. through its Financial Statements in 2019-2021 uses the Economic Value Added approach. EVA at Bank Muamalat Indonesia, Tbk. has increased, except in the second year of research, namely in 2020 there has been a decrease but it is still in a positive EVA state. So it can be said that Bank Muamalat's Economic Value Added in the research period, namely 2019-2021, has an EVA value that is always 0 (positive), and shows that the rate of return generated by the company exceeds the value of capital costs. Based on the presentation and analysis results in the previous chapter, it can be concluded that the value of EVA PT. Bank Muamalat Indonesia Tbk. Period 2019 to 2021 Shows positive economic added value (0). So it can be said that in 2019 to 2021 PT. Bank Muamalat Indonesia Tbk. has been able to create economic added value for the company and increase the wealth of its shareholders. Keywords : Financial Statements, Financial Performance, EVA